Anisotropic Nanoparticles with Controllable Morphologies from Non‐Cross‐Linked Seeded Emulsion Polymerization. Issue 17 (31st July 2013) - Niu, Qun; Pan, Mingwang; Yuan, Jinfeng; Liu, Xiao; Wang, Xiaomei; Yu, Haifeng
<x xml:space="preserve">Abstract</x> A simple and elegant approach to fabricate anisotropic P(VC‐co‐AAEM)/PS nanoparticles with controllable morphologies via emulsifier‐free seeded emulsion polymerization is presented. Non‐cross‐linked P(VC‐co‐AAEM) seeds with hydrophilic surface are first synthesized through copolymerization of vinyl chloride (VC) and acetoacetoxyethyl methacrylate (AAEM), which are used to prepare P(VC‐co‐AAEM)/PS NPs with multiple bulges by SEP of styrene. Electron microscopy observation indicates that the content of AAEM in seeds is crucial to control the phase separation and morphology of the composite NPs. Moreover, the thermodynamic immiscibility between PVC and PS is the driving force for the formation of PS bulges onto the P(VC‐co‐AAEM) seeds. The resultant anisotropic NPs with non‐cross‐linked feature may promisingly serve as compatibilizers for further polymer processing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>